The Effect af Internet on English Learners’ Learning Behavior - Syawal Syawal; Patahuddin Patahuddin; Nasrullah Nasrullah (ELT Worldwide: Journal of English Language Teaching, 2017)
Nowadays internet becomes the most popular information’s source that people use to find information needed. However, it is very crucial that it serves advantages and disadvantages as well.  In this study, the researcher focused on verifying internet disadvantages regarding to its negative effect on leraners’ behaviour. This study was conducted at the Department of English Education, Faculty of Teachers Training and Education, Muhammadiyah University of Parepare utilizing questionnaire, involving the second and fourth semester Learners as the population.  The  samples  were  determined  based  on  simple  random  sampling  in  which  every individual in the population had an equal chance to be chosen as a sample. Findings indicated that most of the learners less creativity, internet addict, violation and plagiarism. Most of the Learners revealed that they prefer to copy data from internet than paste it to fulfill their assignment without editing. However, internet also becomes their alternative learning source better than other learning media. On the contrary, they thought library is not effective to overcome their obstacles in learning.  Lack of idea, attention and brainstorming are considered as some of the causes. Role of lecturer and the used of plagiarism checker software are recommended, as well as the use of citation and reference software.